Influência da exposição à fumaça do cigarro e ao etanol sobre as alterações da mucosa do esôfago induzidas por dieta modificada em camundongos C57BL/6 - Zapaterini, Joyce Regina [UNESP] (2010)
Upper aero digestive tract (UADT) cancer is an important cause of morbidity and mortality worldwide. Chronic alcohol intake and dietary deficiency zinc, tobacco smoking, and gastroesophageal reflux disease are the major risk factors to the UADT cancer. In the present study, we utilized a diet that mimic inadequate zinc intake (Zn-) diet and supplemented it with unconjugated bile deoxycholic acid (DCA), a component associated with gastroesophageal reflux disease and high fat diets. The aim of this study was to assess the additional influence of exposure to cigarette smoke and ethanol intake on the epithelial alterations of the esophagus and tongue induced by Zn-+DCA diet. Male C57BL/6 mice animals were allocated into six groups: Groups 1 to 3 were fed modified diet (Zn-+ 0.2% DCA) and groups 4 to 6 were fed control diet. After 5-weeks, groups 2 and 5 intake ethanol 10% ad libitum and groups 3 and 6 were exposed to cigarette smoke for 15 weeks. All animals were euthanized at the end of week 20 and tongue and esophagus were collected for histological analysis and immunohistochemical analysis of cell proliferation using Ki- 67 marker and cyclooxygenase 2 expression (COX-2). The Zn-+DCA diet treatment trend to increased cell proliferation indexes and the incidence of hyperkeratosis in the tongue and esophagus but not in COX-2 expression. No additional effect of 15-week treatment with ethanol or cigarette smoke was observed. These findings indicate that dietary zinc deficiency supplemented with deoxycolic acid appears to be an important factor of epithelial aggression and that deleterious effect of ethanol and cigarette smoke could be detected in a long-term exposure.